Advance in chimeric antigen receptor T therapy in autoimmune diseases - Ji, Xiaolan; Sun, Yunfan; Xie, Yuyang; Gao, Jianling; Zhang, Ji (Frontiers in Immunology, 2025)
Autoimmune diseases are a group of diseases in which the body’s immune system misrecognizes its own antigens resulting in an abnormal immune response, which can lead to pathological damage to or abnormal functioning of its own tissues. Current treatments are mainly hormones and broad-spectrum immunosuppressants, but these can lead to a decline in the patient’s immunity. Chimeric antigen receptor T (CAR-T) Cell therapy has emerged, and now the structure of CAR has changed from first generation to fourth generation of CAR. The significant achievement of CAR-T therapy to B-cell leukemia has also inspired the treatment of autoimmune diseases, and by investigating the mechanisms of different autoimmune diseases, different designs of CAR-T can be used to specifically treat autoimmune diseases. In this review, we will discuss the therapeutic strategies of CAR-T cells in different autoimmune diseases and the limitations of the treatment.